The role of tumor necrosis factor (TNF) in angiogenesis - Bigda, Jacek; Okrój, Marcin (Contemporary Oncology/Współczesna Onkologia, 2002)
TNF is a pleiotropic, proinflammatory cytokine produced by activated monocytes and macrophages. Its action is mediated by the cell-surface receptor, of which two species have been identified as TNF- R1 or p55 (of molecular weight 55 kDa) and TNF- R2 or p75 (of molecular weight 75 kDa). TNF influences function of immunocompetent cells, production and secretion of other cytokines and induces cytotoxic effect towards different tumor cells. Since it is well known that angiogenesis is the limiting factor of tumor progression and it can be regulated by various cytokines, knowledge on the way particular cytokines modulate angiogenesis can be useful for design of antitumor therapies. TNF is a ligand that can initiate many signaling pathways resulting in production of factors influencing angiogenesis. TNF can also directly affect function of endothelial cells. Reports on the role of TNF in angiogenesis are equivocal and indicate that TNF seems to function as stimulatory or inhibitory agent dependently on the conditions applied in an experiment. Stimulatory action stems from activation of genes coding for proangiogenic factors (e.g. VEGF, FGF, IL-8) and its receptors. Activation of proangiogenic substances is mediated by transcription factors: NFkB, sp-1, c-Jun. TNF-mediated inhibition of angiogenesis results from down-regulation of receptors for proangiogenic factors (IL8-R, flt-1, flk-1, flg) and activation of angiogenesis inhibitors such as angiopoetin-2. Moreover, TNF can influence angiogenesis indirectly by stimulation of other cells, especially macrophages and modulation of adhesion molecules expressed on endothelial cells. Since the high expression of particular integrins on these cells and higher amount of fibronectin in tumor vasculature substratum was found, adhesion is believed to be a very important event in angiogenesis. The results of in vitro and in vivo research suggest two critical variables responsible for TNF effect on angiogenesis: concentration of cytokine and time of exposure of target cells to the cytokine. Low doses of TNF and short time of exposure result in proangiogenic effect, while high doses and longer exposure can act as antiangiogenic conditions.